Transformasi Hidup Baru di Dalam Kristus melalui Pendidikan Agama Kristen (2 Korintus 5:17) - Nadeak, Sanjay Mendra Jubil Kampus; Rehiara, Djad Yehuda; Maryar, Meliaki; Bay, Yepy; Bahabol, Atinus (MAWAR SARON: Jurnal Pendidikan Kristen dan Gereja, 2026)
Generation Alpha is a generation born and raised in the digital world. From a young age, they have been accustomed to gadgets, the internet, and various forms of technology. On the one hand, this progress brings many opportunities, but on the other hand, it also poses serious challenges to character development. Values such as responsibility, patience, and empathy are beginning to be eroded by a culture of instant gratification and digital individualism. Christian education, as a vehicle for shaping faith and values, is called upon to play a relevant role in the character formation of this generation without losing its theological essence. This study seeks to answer the question: how can Christian education shape the character of Generation Alpha in the digital age from a theological and contextual perspective? This study employs a qualitative approach using a literature review method, examining theological and biblical sources as well as the latest research findings on the younger generation and digitalization. The findings indicate that Christian education remains relevant if it is able to integrate the values of faith with a contemporary approach. Character formation through love, exemplary behavior, and mentoring is key, requiring collaboration among families, churches, and Christian schools. Technology is not a barrier but can be an effective tool when used wisely. This study affirms that amidst the challenges of the digital age, Christian education is not only still needed but is actually a source of hope for shaping a generation deeply rooted in Christian values.